Evaluate the Factors Associated with the Choice of Cesarean Section among Pregnant Women - Rasool Gharaaghaji (Journal of Global Pharma Technology, 2017)
Introduction Caesarean section is usually limited to factors that vaginal delivery is not possible or associated with the serious risks to the fetus and mother. So, it is expected a few specific indications forces are an delivery, and the rates do not exceed certain limits. But in our country today, the cesarean rate is reported to be more than acceptable. The aim of this study was to evaluate the social, cultural and demographic factors associated with the choice of delivery method. Methods the population of pregnant women was in cities and villages around Uremia city and the intended sample sizewas299 for pregnant women of which171wereurbanand 128 were rural. Sampling was in classification. Using question naire, data was collected and data was analyzed by SPSS software and logistic regression and Pearson Chi-Square. Results Inferential multi variate statistics and findings indica tea significant association between maternal education and the mother's age and father's occupation and child birth with choosing cesarean, but there was no significant relationship between the place of residence (urbanorrural), father's education, mother's occupation, father's occupation, father's age, wanted and unwanted babies and sex with choosing cesarean. The variables, maternal education, maternal age and rating childbirth were entered. According to the importance of place of residence variable its correlation with mode of delivery was confirmed using the Chi-square test. Conclusion Maternal education, maternal age, parental occupation, rating childbirth andplace of residence (urbanorrural) variables was the most important factors in choosing cesarean section. So, it is necessary to organize training workshops form others with high education and young age that are experiencing their first pregnancy, to reduce cesarean section cost.Keywords: Pregnant women, Cesarean section, vaginal delivery.